HUBUNGAN JENIS DIET, DAYA TERIMA, SISA MAKANAN DAN KEPUASAN PASIEN RAWAT INAP DI RS X JAKARTA - Haerani, Rini Siti; Ronitawati, Putri (UHAMKA PRESS, 2023)
The patient's acceptance of the food served during medication in the hospital is an indicator of the success of hospital services. According to the Ministry of Health of the Republic of Indonesia in 2013, hospital food service was unsuccessful if the patient's plate waste was >20% because the standard said plate waste ≤20% was used as an indicator of nutrition services for every hospital in Indonesia. The study aimed to determine the relationship between the type of diet, food acceptability, plate waste, and patient satisfaction at X Hospital in Jakarta. This research used a descriptive method which is observational and cross-sectional. This study was conducted on 62 patients for 12 days. During the study, the highest treatment diet which is received by the patient is a balanced diet of about 40.3%. This hospital found that plate waste and food acceptability are classified as good, about 77.4%. The food components that are served by the hospital consist of animal protein, plant-based protein, vegetables, and fruit. The results showed that plate waste consisted of 14.2% of rice, 14.2% of animal protein, 8.4% of plant-based protein, 24.9% of vegetables, and 5% fruit. The results of bivariate analysis using the chi-square statistical test indicated no relationship between the type of diet and food acceptability with patient satisfaction. Besides, the statistical test revealed a significant relationship between plate waste and patient satisfaction at X Hospital Jakarta.